Increase in Oxidative Stress as Measured by Cerebrospinal Fluid Lipid Peroxidation During Treatment for Childhood Acute Lymphoblastic Leukemia. Issue 2 (March 2015) - (Ki) Moore, Ida M.; Gundy, Patricia; Pasvogel, Alice; Montgomery, David W.; Taylor, Olga A.; Koerner, Kari M.; McCarthy, Kathy; Hockenberry, Marilyn J.
Abstract : Five-year survival from childhood acute lymphoblastic leukemia (ALL) approaches 90%, but 40% of survivors experience central nervous system (CNS) treatment–related cognitive problems. Despite considerable evidence for cognitive problems, less is known about mechanisms of neurological injury. Our purpose was to investigate oxidative stress, measured by lipid peroxidation, as a mechanism of CNS treatment–related neurological injury. The sample included 55 children (mean age at diagnosis=6.84 y, SD=3.40) who received intrathecal and intravenous chemotherapy for CNS-directed treatment according to Children's Oncology Group protocols. Glycerophospholipids were extracted from cerebrospinal fluid samples obtained at diagnosis and during intrathecal chemotherapy administration. Unoxidized and oxidized phosphatidylcholine (PC) and phosphatidylinositol (PI) were measured by normal phase high-performance liquid chromatography with diode array detection, and analyzed with a general linear model for repeated measures analysis of variance. Compared with the diagnostic cerebrospinal fluid sample, unoxidized and oxidized PC and PI increased significantly across treatment phases. Amount of intravenous methotrexate received was significantly correlated with oxidized PI, and age at time of ALL diagnosis was significantly associated with oxidized PC. These findings support our hypothesis that oxidative stress is a mechanism of neurological injury associated with CNS-directed treatment for ALL.